1993
DOI: 10.1007/bf01772202
|View full text |Cite
|
Sign up to set email alerts
|

The antioxidant defense system of isolated guinea pig Leydig cells

Abstract: Utilization of highly enriched preparations of steroidogenic Leydig cells have proven invaluable for studying the direct effects of various hormones and agents on Leydig cell function in vitro. However, recent work indicates that isolated Leydig cells are often subjected to oxygen (O2) toxicity when cultured at ambient (19%) oxygen concentrations. Because intracellular antioxidants play an important role in protecting cells against oxygen toxicity, we have investigated the intracellular antioxidant defense sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
9
0
1

Year Published

1994
1994
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 29 publications
(24 reference statements)
1
9
0
1
Order By: Relevance
“…Data on antioxidant enzyme activity in whole rat and guinea pig testes [31,50] have been previously reported. As compared to the liver, rat testes express equivalent SOD activity but only 5% of the GPx liver levels and 2% of the liver catalase activity [31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data on antioxidant enzyme activity in whole rat and guinea pig testes [31,50] have been previously reported. As compared to the liver, rat testes express equivalent SOD activity but only 5% of the GPx liver levels and 2% of the liver catalase activity [31].…”
Section: Discussionmentioning
confidence: 99%
“…As compared to the liver, rat testes express equivalent SOD activity but only 5% of the GPx liver levels and 2% of the liver catalase activity [31]. Testicular guinea pig SOD levels were found to be about twice as high as liver SOD in the same species, whereas GPx, GR and catalase were about 60, 5, 300 times less, respectively [50]. The previous studies on testicular tissues did not investigate the precise cellular distribution of these enzymatic activities.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the testis, their activities are very low, 5% and 2%, respectively, as compared with activity in the liver (whereas the superoxide dismutase activity is similar) [5]. Similarly, in cultured guinea pig Leydig cells, lower activities of catalase, GPx, and glutathione reductase are observed, and these Leydig cells are susceptible to H 2 0 2 [4]. In contrast, high expression of PHGPx, which is an antioxidant against phospholipid peroxidation, is observed in the peripheral part of the cytoplasm, the nuclear membrane, and mitochondria in maturating spermatogenic cells in the rat testis [12].…”
Section: Discussionmentioning
confidence: 99%
“…High plasma levels of LH and FSH stimulate Leydig and Sertoli cells, respectively, in the testis. SOD has been reported that to be produced by both Leydig cells [8] and Sertoli cells [11]. The increase in SOD production in the testes of the AZ-dogs may have been directly caused by the high plasma LH and FSH levels or indirectly caused by the increase in T secretion by Leydig cells.…”
mentioning
confidence: 98%
“…Superoxide dismutase (SOD) is known to be the most important antioxidant enzyme in seminal plasma [5], and SOD activity has been detected in canine seminal plasma [2]. Leydig [8] and Sertoli cells [11] have been reported to produce SOD in the testis. Low SOD activity in seminal plasma causes infertility in humans [14].…”
mentioning
confidence: 99%